Evaluation of Drug Prescription Appropriateness for BPJS Kesehatan Patients Against the National Formulary at Noongan Regional General Hospital - Kountur, Gabriela; Lolo, Widya Astuty; Rundengan, Gerald Edward (UNIVERSITAS SAM RATULANGI, 2024)
The prescription of medication in healthcare facilities that collaborate with health social security administering agency refers to the National Formulary. Writing prescriptions that do not comply with the National Formulary can affect the quality of pharmaceutical services in hospitals and may result in rejected prescriptions for patients. The aim of this study was to determine the percentage of drug prescription compliance among BPJS Health patients with the National Formulary during the period of January to June in 2021 and 2022 at noongan regional general hospital, as well as to compare the percentage of prescription compliance between the years 2021 and 2022 during the same period. This research employed a descriptive design with retrospective data collection. The results of the study revealed an average percentage of prescription compliance with the National Formulary of 69.25% during the period of January to June 2021. However, during the period of January to June 2022, there was a decrease in the percentage to 67.22%. Therefore, it can be concluded that the compliance of prescription writing with the National Formulary has not yet reached the established standard.